'Mein cash - ramps and rackets in wartime', 1940 (1940)
1940 1939-1945 "'Mein cash - ramps and rackets in wartime', 1940" [HFR0230], 1940 Pamphlet published by the Independent Labour Party condemning profiteering during the war.